2018
DOI: 10.1186/s12889-018-6266-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with diarrhoeal diseases among children under five in Malaysia: a cross-sectional study 2016

Abstract: BackgroundGlobally, diarrhoea is one of the major causes of morbidity and mortality among children under than 5 years of age. There is a scarcity of published data on acute gastroenteritis (AGE) prevalence in Malaysia among children. This study aims to determine factors associated with diarrhoea in children aged less than 5 years in Malaysia.MethodData from the National Health and Morbidity Survey 2016 conducted by Ministry of Health was analysed. This nationwide survey involved 15,188 children below five year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 15 publications
(8 reference statements)
5
36
4
1
Order By: Relevance
“…Talking about other socioeconomic factors, we found that bloody diarrhea was significantly higher among children belonging to other religion (minority), STs and SCs (marginalized social groups), and those staying in rural areas. These findings are also consistent with studies from different settings [7, 23, 28, 29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Talking about other socioeconomic factors, we found that bloody diarrhea was significantly higher among children belonging to other religion (minority), STs and SCs (marginalized social groups), and those staying in rural areas. These findings are also consistent with studies from different settings [7, 23, 28, 29].…”
Section: Discussionsupporting
confidence: 92%
“…The control variables included in the analysis of (risk of) occurrence of bloody diarrhea are ‘initiation of breastfeeding (within 1 hour, within 1–24 hours, after 24 hours) [27], bottle feeding (yes, no), age of child (below 12 months, 12–23, 24–35, 36–47, 48–59 months) [7], sex of child (male, female), size of child at birth (smaller than average, average and larger) [23]. The analysis also includes literacy of mother (literate, non-literate) [7], exposure to mass media (exposed, unexposed) [28], religion (Hindu, other) [23], caste/tribe (Scheduled Caste (SC) and Scheduled Tribe (ST), other) [29], household wealth status (poor, middle, rich) [28], and place of residence (urban, rural) [7] as control variables.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the LSIS II report and similar studies that examined the factors associated with childhood diarrhea, the present study included the 12 predictor variables below, which were categorized into four levels: the individual, caretaker, household, and village levels [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Environmental variables included in the analysis were source of drinking water, type of toilet facility, and type of floor material. The first two variables are considered as 'Siamese-twins' that potentially influence the occurrence of diarrhoea among children (Hunter, Risebro, Yen, Lefebvre, Lo, Hartemann et al, 2013;Plate, Strassmann & Wilson, 2004;WateAid, 2017;Carr, 2001;Mohammed & Zungu, 2016;Degebasa, Weldemichael & Marama, 2018;Aziz, Ahmad, Abdul Razak, Omar, Kasim, Yusof et al, 2018). Also, the type of floor material of households could determine the level of presence of diarrhoea causing pathogens that children may come into contact with (Exum, 2016;Hashi, Kumie & Gasana, 2016;Bado, Susuman, and Nebie, 2016).…”
Section: Independent Variablesmentioning
confidence: 99%